Evolutionary conservation of acylplastoquinone species from cyanobacteria to eukaryotic photosynthetic organisms of green and red lineages - Ito, Ryo; Endo, Mizuki; Aoki, Motohide; Fujiwara, Shoko; Sato, Norihiro (Frontiers in Plant Science, 2025)
Plastoquinone plays a crucial role in the photosynthetic electron transport system as an electron carrier, transferring electrons from photosystem II to cytochrome b6f complexes. Certain cyanobacteria acylate plastoquinone derivatives, plastoquinol, the reduced form of plastoquinone, and/or plastoquinone-C, the hydroxylated form of plastoquinone to synthesize newly found cyanobacterial lipids, acylplastoquinol and acylplastoquinone-C, the latter of which is known as plastoquinone-B in seed plants. The cyanobacterial genes, slr2103 in Synechocystis sp. PCC 6803 and its ortholog in Synechococcus sp. PCC 7002, encode a bifunctional acyltransferase for the synthesis of both acylplastoquinol and plastoquinone-B. Despite conservation of slr2103 orthologs across a wide range of cyanobacteria, only four cyanobacterial strains, including the two mentioned above, have been identified as producing acylplastoquinol and/or plastoquinone-B. Moreover, the extent to which acylplastoquinone species are distributed in eukaryotic photosynthetic organisms that lack slr2103 orthologs remains largely unknown. Using LC-MS/MS2 analysis of total cellular lipids, this study demonstrates that acylplastoquinol and plastoquinone-B are conserved not only in cyanobacteria with slr2103 orthologs but also in eukaryotic photosynthetic organisms lacking these orthologs, including primary and secondary endosymbiotic algae, and a seed plant. Notably, in eukaryotic photosynthetic organisms as well as in cyanobacteria, these acylplastoquinone species are predominantly esterified with saturated fatty acids. The evolutionary conservation of these acylplastoquinone species suggests replacement of slr2103 orthologs by alternative gene(s) responsible for their synthesis at least once after the primary endosymbiotic event in the evolution of photosynthetic organisms. The persistent conservation of acylplastoquinone species throughout the evolution likely reflects their critical physiological roles.